2013
DOI: 10.1039/c3em00209h
|View full text |Cite
|
Sign up to set email alerts
|

Real-time particle monitor calibration factors and PM2.5 emission factors for multiple indoor sources

Abstract: Indoor sources can greatly contribute to personal exposure to particulate matter less than 2.5 μm in diameter (PM2.5). To accurately assess PM2.5 mass emission factors and concentrations, real-time particle monitors must be calibrated for individual sources. Sixty-six experiments were conducted with a common, real-time laser photometer (TSI SidePak™ Model AM510 Personal Aerosol Monitor) and a filter-based PM2.5 gravimetric sampler to quantify the monitor calibration factors (CFs), and to estimate emission fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
58
4

Year Published

2016
2016
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(65 citation statements)
references
References 22 publications
3
58
4
Order By: Relevance
“…Potentially, also, is that the respondents may have misclassified the presence of smoke-free rules in their homes. Implementation of objective measures of tobacco smoke exposure might be useful in further studies [63,64,65,66]. The cross-sectional design is another limitation of the study as it tends to make observations at a single point in time, which prevents the observation of changes in ETS exposure or smoke-free homes enforcement over longer periods of time [43].…”
Section: Study Limitations and Strengthmentioning
confidence: 99%
“…Potentially, also, is that the respondents may have misclassified the presence of smoke-free rules in their homes. Implementation of objective measures of tobacco smoke exposure might be useful in further studies [63,64,65,66]. The cross-sectional design is another limitation of the study as it tends to make observations at a single point in time, which prevents the observation of changes in ETS exposure or smoke-free homes enforcement over longer periods of time [43].…”
Section: Study Limitations and Strengthmentioning
confidence: 99%
“…Therefore, most of these instruments are used indoors or in situations where particle composition remains constant. Numerous studies have been carried out to analyze the calibration of different kinds of PM2.5 [7,8,9]. It is a great challenge to accurately estimate PM2.5 mass concentration for diverse kinds of PM2.5.…”
Section: Introductionmentioning
confidence: 99%
“…In general, indoor PM 2.5 is influenced by direct emissions from indoor sources (e.g., cooking, smoking, and candle burning) (Jones et al, 2000;Dacunto et al, 2013), ventilation supplies from outdoor sources (Zhao et al, 2015), and transport or transformation processes within indoor environments (e.g., mixing, inter-zonal transport, re-suspension, coagulation, and phase change) (Nazaroff, 2004). The indoor/outdoor relationship studies of PM species showed that major chemical components, including organic and elemental carbon (OC/EC), water soluble ions, and metal elements in indoor PM 2.5 were greatly influenced by outdoor sources (Lim et al, 2011;Cao et al, 2012;Hassanvand et al, 2014).…”
Section: Introductionmentioning
confidence: 99%